Perturbation on gut microbiota impedes the onset of obesity in high fat diet-induced mice - Yu, Zhongjia; Yu, Xiang-Fang; Kerem, Goher; Ren, Pei-Gen (Frontiers in Endocrinology, 2022)
High-calorie intake has become one of the most common reasons causing dietary obesity, which eventually develops to type 2 Diabetes Mellitus (T2DM). Microbiota, along with the length of the gastrointestinal tract, is related to metabolic disorders, but its shifts and following impact on metabolic disorders due to external perturbation are still unclear. To evaluate shifts of microbiota from proximal to the distal intestine and their impact on metabolic disorders, we profiled jejunal and colonic microbiota with the perturbation using high salt (HS) and antibiotic-induced microbiota depletion (AIMD) in diet-induced obesity (DIO) mice, as well as analyzed the association with parameters of both obesity and blood glucose. After ten weeks of feeding, DIO mice with HS intake and AIMD failed to develop obesity. The DIO mice with HS intake had T2DM symptoms, while the AIMD DIO mice showed no significant difference in blood glucose parameters. We observed that the jejunal and colonic microbiota had shifted due to settled perturbation, and jejunal microbiota within a group distributed more dispersive than colonic microbiota. After furtherly analyzing jejunal microbiota using quantified amplicon sequencing, we found the absolute abundance of Colidextribacter (R=0.695, p=0.001) and Faecalibaculum (R=0.631, p=0.005) in the jejunum was positively correlated with the changes of BW and FBG levels. The predicted pathway of glucose and other substances' metabolism significantly changed between groups (p<0.05). We demonstrated that the onset of obesity and T2DM in DIO mice is impeded when the gut microbiota are perturbated; thus, this pathogenesis is dependent on the gut microbiota.